Essays on Contemporary Psychometrics - van der Ark, L. Andries; Emons, Wilco H. M.; Meijer, Rob R. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book 'Essays on Contemporary Psychometrics' provides an overview of contemporary psychometrics, the science devoted to the advancement of quantitative measurement practices in psychology, education and the social sciences. The volume consists of four parts, each having several chapters on cutting-edge work in the field. Part I, General Perspectives on Psychometrics, includes expert views on topics such as psychological models vs. measurement models, using tests in decision making, artificial intelligence, and psychometric network models. Part II, Factor Analysis and Classical Test Theory, the type of psychometrics that is still used most often in the social and behavioral sciences, includes state-of-the-art contributions on test-score reliability, change-score reliability, handling missing data in principal component analysis, test equating, and conditional standard errors of measurement. Part III, Item Response Theory, the leading form of psychometrics in modern educational measurement, includes discussions of sampling from many conditional distributions, transparent score reporting, nonparametric item response theory, and targeted testing. Part IV, New Psychometrics, discusses recently developed ideas beyond classical test theory and item response theory, including topics related to computer adaptive testing, response-time modelling, validity indices, diagnostic classification models, and the sparse latent class model for ordinal measurements. Together, these four parts provide an overview of the current state-of-the-art in psychometrics in educational measurement. They are a valuable source of information for graduate students who (intend to) study psychometrics and need an overview of the field, and for researchers interested in the current developments in the field. Chapters [3], [5], [8], [16] and [19] are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.
Part I. General Perspectives on Psychometrics. 1. Early Roots of Psychometrics Before Francis Galton (Willem J. Heiser) -- 2. The Janus Face of Psychometrics (Paul De Boeck and L. Robert Gore) -- 3. Psychological and Educational Testing and Decision Making: The Lack of Knowledge Dissemination in Textbooks and Test Guidelines (Rob R. Meijer, A. Susan M. Niessen, and Marvin Neumann) -- 4. Trustworthy Artificial Intelligence in Psychometrics (Bernard P. Veldkamp) -- 5. Psychological Constructs as Organizing Principles (Denny Borsboom) -- Part II. Factor Analysis and Classical Test Theory. 6. A New Expression and Interpretation of Coefficient Omega Under the Congeneric One-Factor Model (David J. Hessen) -- 7. A Factor Analysis Approach to Item-Level Change Score Reliability (Dylan Molenaar) -- 8. Handling Missing Data in Principal Component Analysis Using Multiple Imputation (Joost R. van Ginkel) -- 9. Quantifying the Bias of Non-Linear Equating and Score Transformations (Matthias von Davier and Brian Clauser) -- 10. Examination of Test Characteristics Effect on Coefficient ga (Band Coefficient (S} (B(Terry Ackerman, Ye Ma, and Richard Luecht) -- 11. Methods for Estimating Conditional Standard Errors of Measurement and Some Critical Reflections (Wilco H. M. Emons) -- Part III. Item Response Theory. 12. Composition Algorithms For Conditional Distributions (Maarten Marsman, Timo B. Bechger, and Gunter K. J. Maris) -- 13. To a or Not to a: On the Use of the Total Score (Bas T. Hemker) -- 14. A Bayesian Test for the Association of Binary Response Distributions (Rudy Ligtvoet) -- 15. Efficiency and Effectiveness of Teacher Informed Targeting Testing from Different Perspectives (J. Hendrik Straat, Renske E. Kuijpers, Kimberley Lek, and Wilco H. M. Emons) -- Part IV. New Psychometrics. 16. The Hierarchical Model for Response Times: Advantages, Limitations, and Risks of Its Use in Measurement Practice (Jesper Tijmstra and Maria Bolsinova) -- 17. Computer-Adaptive Testing with Fewer Assumptions (Jules L. Ellis) -- 18. Validity Indices for Interpreting Informant Discrepancies in ADHD Assessment (Judith M. Conijn, Mengdi Chen, Hanneke van Ewijk, and L. Andries van der Ark) -- 19. Computerized Adaptive Testing Without IRT for Flexible Measurement and Prediction (L. Andries van der Ark and Niels Smits) -- 20. On the Relationship Between Unidimensional Item Response Theory and Higher-Order Cognitive Diagnosis Models (Jimmy de la Torre and Kevin Carl Santos) -- 21. A Sparse Latent Class Model for Polytomous Attributes in Cognitive Diagnostic Assessments Siqi He, Steven A. Culpepper, and Jeffrey A. Douglas -- Subject index.s
Keywords: Educational tests and measurements; Psychometrics; Educational psychology; Assessment and Testing; Psychometrics; Educational Psychology